Ethnobotanical study of plants used in the management of benign prostate hyperplasia in Ilorin, Nigeria (2023)
Background: Benign Prostate Hyperplasia (BPH) is a prevalent illness in older men. It is a condition where the prostate becomes enlarged and blocks the ease of urine passage out of the bladder. Around 50% of the male population develops symptoms of BPH around 51- 60 years of age. Current therapeutic management options come with undesirable side effects like weight gain, dizziness, and impotence, hence, the need to source for safer alternatives initiated by the acquisition, recording, and preservation of traditional knowledge of medicinal plants. Objective: This study aims to preserve indigenous knowledge by documenting medicinal herbs in use as therapy for BPH. Materials & method: Ethnobotanical survey was carried out in the study areas through interviews using a semi structured questionnaire. Respondents included elderly members of the communities, herbalists, and practitioners of traditional medicine. Quantitative ethnobotany index (Use value index) and descriptive statistics were used to analyse data. Results: 50 respondents were interviewed, 64% were Herb sellers, 22% TMPs, Others 14%. 37 plants belonging to 24 plant families were mentioned in the survey. Methods of preparation of recipes mentioned includes: maceration (37%), decoctions (52%), juice (7%), infusions and paste/powder (4%). Method of administration were majorly oral route. The plant family Fabaceae (19%) had the highest representation. This was followed by the families Annonaceae (8%), Euphorbiaceae (6%), Curcubitaceae, Menispermaceae, Combretaceae, Apocynaceae and Rutaceae with 5% each. Other plant families represented 42% of the total number of plants mentioned. Conclusion: The study areas are endowed with abundant flora which serves as a repository for researchers in the quest to develop less toxic drugs with little or no side-effect for the management of BPH.